TRANSITION TO EMPLOYMENT: INSTRUCTIONAL STRATEGIES OF SPECIAL EDUCATION TEACHERS FOR STUDENTS WITH HEARING IMPAIRMENT (Proceedings of International Conference on Special Education, 2023)
There is an increase in the population of people with disabilities which emphasises issues concerning their inclusion in essential societal functions. For example, in the Philippines, these issues manifest in a low participation rate in jobs and the preparedness of students to transition from school to employment. Special education (SPED) teachers prepare these individuals to transition to employment through meaningful instructional strategies. The study aimed to determine the instructional strategies employed by SPED teachers to equip students with hearing impairment to transition to employment. Using a single case study design, accounts of SPED teachers of students with hearing impairment in a postsecondary educational institution in the Philippines were collected. Data collected through key informant interviews and observations revealed that the instructional strategies of SPED teachers include the use of visual aids and immersion of the students with sign language and assessments as supporting strategies. The instructional strategies of the SPED teachers target necessary skills for employment, such as communication skills, perseverance, and discipline as soft skills and business administration and computer technology as hard skills. Experiences of teachers, which revolve around employment together towards shared goals, influence the instructional strategies of teachers. Moreover, these experiences, especially the negative reality of the employment of students with hearing impairment, also shape the pedagogical decisions of teachers in using effective instructional strategies.